ANALISIS KOMPARASIDAN DAYA SAING EKSPOR KOPI ANTAR NEGARA ASEAN DALAM PERDAGANGANBEBASASEAN TAHUN 2002-2012 - Gusti Ayu Made Dian Rianita (Jurnal Ekonomi Trisakti, 2022)
This study aims to analyze the comparative and coffee export competitiveness among Asean countries in the ASEAN free trade in the year 2002-2012. In addition, to compare studies using the Revealed Comparative Advantage (RCA) and Panel Data . The factors used to see coffee exports include coffee prices ASEAN countries of origin, countries of origin of coffee production, exchange rate, acreage planted coffee origin countries, GDP per capita in the world. The results showed only country RCA Indonesia and Vietnam who have strong competitiveness on the export of coffee ( RCA > 1 ), Thailand and Phillipina has particularly RCA < 1 so it does not have a strong competitive edge. Test results of panel data shows the export of coffee in four ASEAN countries (Indonesia, Thailand, Vietnam, and the Philippines) are significantly influenced by the total production of coffee, coffee prices, and the GDP per capita in the world. These results using the alpha of ten percent. And in between all independent variables are used, the exchange rate and the planting area that does not have a statistically significant effect on the export of coffee in four ASEAN (Indonesia, Thailand, Vietnam, and Phillipina.